PEMBUATAN DAN PENGELOLAAN TAG LOKASI USAHA DI GOOGLE MAPS BAGI PELAKU INDUSTRI TAHU LEDOK KULON BOJONEGORO - Muhammad Agustino; Reza Anggapratama; Eka Ilham Firmansyah; Iqbal Indrawan Santoso (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
This community service program was carried out in Ledok Kulon Village, Bojonegoro District, Bojonegoro Regency, with the aim of improving digital literacy and the marketing capabilities of tofu industry entrepreneurs through the use of Google Maps as a business promotion platform. Based on initial observations, business owners in the area had not utilized digital technology optimally and still relied heavily on traditional marketing methods. The activities consisted of preparation, socialization, digital literacy training, hands-on practice in creating a Google Business Profile, verification assistance, monitoring, and evaluation. A hands-on mentoring approach was implemented to ensure participants gained direct learning experiences and were able to manage their business profiles independently. The results showed that 22 business owners successfully created and activated their business location tags on Google Maps, indicating the effectiveness of the program in enhancing participants’ digital capabilities. Documentation and verification demonstrated that all business profiles appeared in Google Maps searches and had begun receiving initial user views. This program has had a direct impact on increasing business visibility and has provided a foundation for the digital transformation of MSMEs in the village. Thus, this community service activity contributes to strengthening the competitiveness of local MSMEs through the use of simple, low-cost, and sustainable information technology